HUBUNGAN KECERDASAN SPIRITUAL ISLAM, KECERDASAN EMOSIONAL DAN PRESTASI BELAJAR MAHASISWA KEPERAWATAN DI UNIVERSITAS BINA BANGSA - Nova Tri Handriyanto; Nova Maulana; Maratu Solihah (Jurnal Ilmiah Keperawatan, 2023)
ABSTRACT Learning achievement is an indicator of student development and progress in mastering the lessons that the teacher has given to students. In the educational world of the teaching and learning process, teachers must balance the Intellectual Quint and the Spiritual Quint in order to achieve students who are successful emotionally and academically. This research aims to determine the relationship between Islamic spiritual intelligence and emotional intelligence with learning achievement in nursing students at Bina Bangsa University. The method used in this research is quantitative methods. The population in this study were all nursing study program students class of 2023 at Bina Bangsa University. The total population was 148. The sampling technique in this study used purposive sampling with a sample size of 60 respondents. Data were analyzed using the Kendall Tau statistical test and multivariate analysis using multiple linear regression. Based on the results of the Kendall Tau test, the calculated r value is (Islamic spiritual intelligence) 0.399, (emotional intelligence) 0.587. Multivariate results are 17,825 with asymp numbers. Sig. in each measurement (emotional intelligence was 0.000 while (Islamic spiritual intelligence) was 0.082. These results can be concluded that there is a relationship between Islamic and emotional spiritual intelligence and learning achievement in Bina Bangsa University nursing students.